2018
DOI: 10.2174/1570180814666170810120634
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis and Cytotoxic Activity of Spiro(oxindole-3-3'- pyrrolidine) Derivatives

Abstract: Background: Spiro[pyrrolidine-3,3'-oxindole] compounds are reported to be highly bioactive natural and synthetic products. Initially, spirooxindole alkaloids were isolated from plants of the Apocynaceae and Rubiaceae families, which were found to have a common scaffold, spiro[pyrrolidine-3,3'-oxindole], exhibiting anticancer activities., we specifically aimed at the synthesis, characterization and anticancer activity of novel spiro[pyrrolidine-3,3' -oxindole] derivatives, compounds 6a-c and 7. Methods: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Synthesis, characterization and anticancer activity of Spiro[pyrrolidine-3,3'oxindole] derivatives, compounds 31 was carried out by Konyar et al [112]. Cytotoxic effects of the compounds were determined on Huh7, MV, HCT116 and MCF7 cancer cell lines by the NCI-60 Sulforhodamine B Assay, using (S)-(+)-Camptothecin as a positive control.…”
Section: Spiro-indole Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis, characterization and anticancer activity of Spiro[pyrrolidine-3,3'oxindole] derivatives, compounds 31 was carried out by Konyar et al [112]. Cytotoxic effects of the compounds were determined on Huh7, MV, HCT116 and MCF7 cancer cell lines by the NCI-60 Sulforhodamine B Assay, using (S)-(+)-Camptothecin as a positive control.…”
Section: Spiro-indole Derivativesmentioning
confidence: 99%
“…Generally, target compounds showed better cytotoxic activities against the MCF7 and HCT116 cancer cell lines. It was found that compound 31 exhibited the most potent inhibitory activity with IC50 values of 4.8 μM, 3.9 μM, 14.9 μM and 8.2 μM against the MCF7, HCT116, MV and Huh7 cell lines, respectively [112].…”
Section: Spiro-indole Derivativesmentioning
confidence: 99%